Design, Synthesis, and Evaluation of an 18F‐Labeled Radiotracer Based on Celecoxib–NBD for Positron Emission Tomography (PET) Imaging of Cyclooxygenase‐2 (COX‐2). Issue 10 (18th August 2015) - Kaur, Jatinder; Tietz, Ole; Bhardwaj, Atul; Marshall, Alison; Way, Jenilee; Wuest, Melinda; Wuest, Frank
Abstract A series of novel fluorine‐containing cyclooxygenase‐2 (COX‐2) inhibitors was designed and synthesized based on the previously reported fluorescent COX‐2 imaging agent celecoxib–NBD (3; NBD=7‐nitrobenzofurazan). In vitro COX‐1/COX‐2 inhibitory data show that N‐(4‐fluorobenzyl)‐4‐(5‐p‐tolyl‐3‐trifluoromethylpyrazol‐1‐yl)benzenesulfonamide (5; IC50=0.36 μM, SI>277) and N‐fluoromethyl‐4‐(5‐p‐tolyl‐3‐trifluoromethylpyrazol‐1‐yl)benzenesulfonamide (6; IC50=0.24 μM, SI>416) are potent and selective COX‐2 inhibitors. Compound 5 was selected for radiolabeling with the short‐lived positron emitter fluorine‐18 (18F) and evaluated as a positron emission tomography (PET) imaging agent. Radiotracer [18F]5 was analyzed in vitro and in vivo using human colorectal cancer model HCA‐7. Although radiotracer uptake into COX‐2‐expressing HCA‐7 cells was high, no evidence for COX‐2‐specific binding was found. Radiotracer uptake into HCA‐7 tumors in vivo was low and similar to that of muscle, used as reference tissue.